HYPOGLYCEMIC EFFECT TEST OF SWEET POTATO (Ipomoea batatas) LEAVES ETHANOL EXTRACT AGAINTS BLOOD GLUCOSE LEVEL OF ALLOXAN-INDUCED WHITE MALE WISTAR RAT (Rattus norvegicus) - ., Vidia Asriyanti (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Hot water infusion of sweet potato (Ipomoea batatas) leaves empirically used as oral antidiabetic. Sweet potato leaves contain manypholyphenol compound which can reduce blood glucose level. Objective:This study investigated the hypoglycemic effect and effective dose ofsweet potato leaves ethanol extract compared to metformin in alloxaninducedmale Wistar rat. Method: The study was an in vivo experimental.Thirty male Wistar rats was randomly divided into 5 experimental groupsthose were negative control (CMC 0,5%), positive control (metformin), dose 1 (1,4 g/kgBW extract), dose 2 (2,8 g/kgBW extract), and dose 3 (5,6 g/kgBW extract). The rats were induced by alloxan and the treatment eachgroup was given for 7 days. The resulting data is analyzed with One-wayAnova test then continued with LSD Post Hoc test. Result: Based on thephytochemical screening, sweet potato leaves ethanol extract containflavonoid and tannin. Statistical analysis showed significant differencebetween average of fasting blood glucose level from control group(negative and positive) with dose 1 group (p<0,05) in post test fastingblood glucose measurement. Effective dose of sweet potato leaves extractwas 700 mg/200 gBW. Conclusion: Ethanol extract of sweet potatoleaves was suspected had blood glucose reduction effect in alloxaninducedmale Wistar rat with effective dose at 700 mg/200 gBW whichshowed better effect than metformin.Key words: Ipomoea batatas, sweet potato leaves ethanol extract, alloxaninduction, phytochemical screening, blood glucose reduction.